(untitled) (Human Factors in Design, 2012)
This paper discusses a bibliographic review portraying the product armchair versus humans. There was a feeling that this artifact is recognized as an integral part of the environment artificially produced by man, as it is the transportation segment, however, it is in a period little shorter than a decade that, in Brazil, the first studies on how its design can affect or interfere in the physical comfort of its users began. This study proposes to refer to theoretical approaches of the concept of comfort pervaded by ergonomics assumptions and by human factors.